Study on fracture toughness with different thicknesses CT specimen - S. Fan; Q. Wang; K. Guan (Ubiquity Proceedings, 2018)
The material selected for this study was a WELDOX 900 steel plate. This paper analyzed the size effect of fracture toughness based on experimental results and finite element numerical simulation results. In addition, J-integrals of different thicknesses were investigated and the relational expression between them was acquired in this study. The main conclusions are as follows: Firstly, the formula between the ductile fracture toughness J0.2 and the specimen thickness was obtained. It proposed a method for predicting the fracture toughness of plane strain state using thin specimens of several thicknesses based on this formula. Secondly, the fracture toughness values of the materials were obtained by finite element numerical simulation. And it was found that the distribution of stress triaxiality near the crack tip could well explain the variation of fracture toughness with thickness.